Physicochemical Characterization of Mritasanjeevana Rasa Prepared with Hingul and Rasa-Sindura - Varad Charkha; Pradeep Kumar Prajapati; Mohar Pal Meena (Wolters Kluwer Medknow Publications, 2024)
Introduction: Mritasanjeevana Rasa (MR) is a herbo-mineral formulation mentioned in Brihat Rasaraja Sundara, an ancient text of Rasashastra written by Dattaram Choube. MR contains Hingula (Cinnabar) as its main ingredient along with Vatsanabha (Aconitum ferox Wall ex Ser.), Jayapala (Croton tiglium L.), and Tankana (Borax). Hingula is chemically similar to Rasasindura (RS) as per modern concept (a classical preparation in Rasa Shastra) as both are red sulfides of mercury (α-HgS). Methods: MR-classical (MRC) was prepared as per textual guidelines. MR-modified (MRM) was also prepared as per the same guidelines. Hingulottha Parada was used for preparation of RS. Physicochemical characterization including ICP-MS, fourier transform-infrared spectroscopy, high-performance thin layer chromatography, thermo gravimetric analysis (TGA), and particle size analysis was performed for both samples. Results: MRC and MRM showed similar results in pH value, moisture content, ash values, water-soluble extract, hardness test, friability test, and disintegration time. ICP-MS revealed that mercury and sulfur are the main elements present in MRC and MRM. X-ray diffraction analysis confirmed the presence of sodium sulfate and mercuric sulfide (HgS) in both the samples. Both revealed scaly crystalline structures. Their average particle size was between 800 and 900 nm with the lowest particle size of 103 nm and 134 nm, respectively. FTIR analysis revealed that MRC and MRM samples contain functional groups such as C-O-C, S = O, and C-H. TGA analysis suggests that MRM showed better stability than MRC throughout the heating phase. Conclusion: The present study shows that MR and its modified formulation do not affect the Physicochemical characteristics of the final compound to a considerable extent.